Assessing patiromer utilization and associated serum potassium changes in US veterans with prior sodium polystyrene sulfonate exposure. Issue 9 (3rd March 2023) - Patel, Shardool; Pinnell, Derek; Qualls, Joshua; Rathod, Anitha; Chen, Wei; Boutin, Sylvie; Woods, Steven D.; Kovesdy, Csaba P.; Tangri, Navdeep; Sauer, Brian C.
Abstract : Untreated chronic hyperkalemia is associated with an increased risk of mortality. Novel potassium binders (e.g., patiromer) are new additions to the clinician's armamentarium. Prior to their approval, clinicians often considered trialing sodium polystyrene sulfonate. The study objective was to assess patiromer utilization and associated changes in serum potassium (K+) in US veterans with prior sodium polystyrene sulfonate exposure. This was a real-world observational study of US veterans with chronic kidney disease and a baseline K+ ≥ 5.1 mEq/L, initiated on patiromer between January 1, 2016, and February 28, 2021. The primary endpoints were patiromer utilization (dispensations and treatment courses), and K+ change at 30-, 91-, and 182-day follow-up (FU) intervals. Patiromer utilization was described using Kaplan–Meier probabilities and the proportion of days covered. Descriptive changes in population average K+ were obtained from a pre-post design using single-arm within-patient pre-post lab pairs and paired t tests. Two hundred five veterans met the study criteria. We observed an average of 1.25 (95% CI, 1.19–1.31) treatment courses and a median treatment duration of 64 days. Fifty veterans (24.4%) had >1 course, and 17.6% of patients remained on their initial patiromer treatment course until the end of the 180-day FU. The mean K+ value was 5.73 mEq/L (5.66–5.79) at baseline, 4.95 mEq/L (95% CI, 4.86–5.05) at the 30-day interval, 4.93 mEq/L (95% CI, 4.84–5.03) at the 91-day interval, and 4.9 mEq/L (95% CI, 4.8–4.99) at the 182-day interval. Novel potassium binders (e.g., patiromer) are newer chronic hyperkalemia management tools for clinicians. The average population K+ decreased to <5.1 mEq/L at all follow-up intervals. Patiromer appeared to be well tolerated with nearly 18% of patients remaining on their initial treatment course during the entire 180-day FU period. The median treatment duration was 64 days and approximately 24% of patients initiated a second course during FU.